Methacholine challenge : Comparison of two methods - COCKCROFT, Donald W; DAVIS, Beth E; TODD, David C; SMYCNIUK, Audrey J (Chest, 2005)
Guidelines for the 2-min tidal-breathing and the five-breath dosimeter methods for methacholine challenge have recently been published by the American Thoracic Society (ATS). Although subjects are exposed to twice as much aerosol at any given concentration during the tidal-breathing method compared to the dosimeter method, they were thought to give equivalent results. To compare the 2-min tidal-breathing and the five-breath dosimeter methacholine challenges. Tertiary care university-based bronchoprovocation laboratory. Forty subjects with currently symptomatic asthma. The two methacholine tests were done in random order on separate days at the same time of day at 1- to 7-day intervals. The dosimeter provocation concentration of methacholine causing a 20% fall in FEV(1) (PC(20)) was almost twice that of the tidal-breathing PC(20): 2.4 mg/mL vs 1.3 mg/mL (paired t test, p < 0.00005). The difference was greater in those with mild airway hyperresponsiveness (AHR) [PC(20) > 1.0 mg/mL; 3.2-fold] compared to those with moderate AHR (PC(20) < 1.0 mg/mL; 1.6-fold) [p = 0.04]. Three subjects with mild asthma and mild AHR (tidal-breathing PC(20), 1.9 to 4.3 mg/mL) had a nonmeasurable PC(20) (> 32 mg/mL) with the dosimeter. The tidal-breathing method, which exposes the subject to twice as much aerosol at each concentration, produced approximately twice the response. The total lung capacity maneuvers with breathhold during the dosimeter method may inhibit the response in some patients with asthma.